A good house for children : a novel - Collins, Kate, 1951- (Mariner Books, 2023)
"Once upon a time Orla was: a woman, a painter, a lover. Now she is a mother and a wife, and when her husband Nick suggests that their city apartment has grown too small for their lives, she agrees, in part because she does agree, and in part because she is too tired to think about what she really does want. She agrees again when Nick announces with pride that he has found an antiquated Georgian house on the Dorset cliffs--a good house for children, he says, tons of space and gorgeous grounds. But as the family settles into the mansion--Nick absent all week, commuting to the city for work--Orla finds herself unsettled. She hears voices when no one is around; doors open and close on their own; and her son Sam, who has not spoken in six months, seems to have made an imaginary friend whose motives Orla does not trust. Four decades earlier, Lydia moves into the same house as a live-in nanny to a grieving family. Lydia, too, becomes aware of intangible presences in the large house, and she, like Orla four decades later, becomes increasingly fearful for the safety of the children in her care. But no one in either woman's life believes her: the stories seem fanciful, the stuff of magic and mayhem, sprung from the imaginations of hysterical women who spend too much time in the company of children. Are both families careening towards tragedy? Are Orla and Lydia seeing things that aren't there? What secrets is the house hiding?"--